Analisis Proses Pascapanen Kopi di Pusat Pelatihan Pertanian dan Pedesaan Swadaya (P4S) Kopi Gunung Ikamaja Kecamatan Sumberjaya Kabupaten Lampung Barat - Rangga, Kordiyana K.; Pardani, Nanda (Jurnal Agro Industri Perkebunan, 2024)
The post-harvest coffee process is vital in determining the quality and quantity of coffee production. Problems that often occur in the post-harvest coffee process are incomplete or overcooked fermentation, improper drying process, high water content, improper roasting process, and inappropriate use of resources. For this reason, it is important to carry out proper processing in the post-harvest coffee process so that the quality of the coffee can be optimal. This research aims to analyze the post-harvest process of robusta coffee and identify post-harvest coffee facilities and infrastructure at P4S Kopi Gunung Ikamaja. The types of data used are primary data and secondary data. The data collection methods used in this research are expert interviews and active participation observation. The results of the study show that there are post-harvest coffee processes that do not comply with the provisions for post-harvest processing according to Minister of Agriculture Regulation Number 52/Permentan/OT.140/9/2012. In natural processing processes, those that are appropriate are the sorting, drying, horn stripping, roasting, and fine grinding stages, while those that are not appropriate are the packaging process. Honey process processing is in accordance with Minister of Agriculture Regulation Number 52/Permentan/OT.140/9/2012. The full wash process is not by Agriculture Ministerial Decree Number 52/Permentan/OT.140/9/2012 at the fermentation stage. Facilities and infrastructure based on building location are not yet appropriate; however, based on tools and machines and based on containers and packaging, they are by the provisions of Minister of Agriculture Number 52/Permentan/OT.140/9/2012.